Moving Towards Lifelong Learning in Rural New Zealand: A Study of Two Towns - John Benseman (Journal of Research in Rural Education, 2006)
Like most other Western countries, New Zealand has been undergoing considerable change in its rural communities for some decades. Alongside the changes in rural New Zealand, there has been what many commentators argue, a paradigm shift in education from a "front-loaded" model dominated by schooling to one of lifelong learning. This article examines the nature of these changes in rural life and education and then examines how well 2 New Zealand rural communities are faring in terms of lifelong learning ideals. Based on 40 in-depth interviews and site visits, the study identifies both positive developments and some key issues that are hindering the development of lifelong learning.